FACTORS RELATING TO PERMANENCE IN THE DISTANCE GRADUATION COURSE “BACHARELADO EM DESENVOLVIMENTO RURAL - PLAGEDER” OF UAB/UFRGS - Fontana Dias, Fernando (2021)
This article was done with a goal: develop the knowledge about one of most important phenomena of distance learning, the permanence of students, relating course offer aspects with the students opinion about permanence factors, considering the importance of this modality in the present days. The objective was to understand the way in which organizational and motivational factors contributed to the permanence and conclusion of the third edition of the PLAGEDER distance course, analyzing the influence of factors related to the permanence in the course, identifying and understanding the obstacles of the students to the conclusion of the course. Thus, the following research problem was answered: in what way organizational and motivational factors reflect in the permanence and conclusion of the distance learning course in Rural Development - PLAGEDER, in its third edition. The research involved quantitative and qualitative analysis. Primary and secondary data were used in the data collection. Questionnaires were used both for the students of the course and for the actors involved with the course offer. The work also relied on the use of observation for data collection. The results showed a significant difference of the permanence in the different poles where the course was offered, varying from 16% to 54.76%. In general, it was possible to verify that factors related to face-to-face activities were considered more important by the students than the factors related to distance activities for the decision to remain in the course.The relationship between the limited time available for the study and the lack of self-discipline, as obstacles to the completion of the course, compose an interesting find presented in the results.